(untitled) (Journal of Global Arts Studies, 2024)
Background: Liebesträume No. 3 is a piano composition adapted by Franz Liszt from a series of love poems and consists of three pieces. Objective: Exploring the artistic characteristics and performance essentials of this work possesses important research value and practical significance for understanding Liszt’s compositional style. Methods: This study takes the third piece of Liebesträume No. 3 as the research object. Through the collection and organization of related publications and literature, combined with the author’s own piano performance practice, the study conducts theoretical and comparative analyses of the work. Results: The research finds that Liebesträume No. 3 demonstrates distinctive artistic characteristics, including a close correspondence between poetry and music, a deep integration of music and emotion, and a prominent symphonic style of treatment. Conclusion: In order to comprehensively and accurately reveal the artistic qualities and performance methods of the third piece of Liebesträume No. 3, performers should not only analyze its artistic characteristics but also deeply master key technical aspects such as octave chord treatment, the performance of colorful musical passages, and pedal techniques. Through overall artistic control of the work, performers can more accurately express the composer’s longing for and pursuit of love. Only through continuous refinement of performance techniques can performers freely integrate emotional connotation with technical expression, achieve emotional resonance with audiences, and fully demonstrate the enduring artistic charm and profound influence of Liszt’s “Dream of Love.”